Cross-Linguistic and Multicultural Effects on Animal Fluency Performance in Persons With Aphasia. - Sung, Jee Eun; Shin, Junyoung; Scimeca, Michael; Li, Ran; Kiran, Swathi (American Journal of Speech-Language Pathology)
Purpose: The current study examined the impact of cross-linguistic and cultural differences on an animal fluency task between Korean- and English-speaking persons with aphasia (PWA) and neurologically intact older adults (OAs). Specifically, we investigated the influence of zodiac animals on word retrieval, given their cultural familiarity in East Asia, hypothesizing that Korean speakers have a higher likelihood of producing zodiac animals compared to English speakers. Method: Sixty-seven PWA (30 English-speaking, 37 Korean-speaking) and 30 OAs (15 per language group) completed an animal fluency task. Analyses focused on three approaches: total correct responses, culturally specific responses (zodiac animals and ratio of zodiac animals), and an item-level comparison of language-general and language-specific items to identify animal items that could differentiate between the language groups. Results: Korean speakers, both with and without aphasia, produced a greater proportion of zodiac animals compared to English speakers. Conversely, English speakers demonstrated greater semantic diversity in animal responses than Korean speakers. Conclusions: Both PWA and OA groups demonstrated differential patterns in producing zodiac animals, depending on their language and the culture. These findings shed light on the importance of considering cultural and linguistic diversity during aphasia assessment of word retrieval difficulties.